INVESTIGATING MARITIME CADETS’ DIFFICULTIES IN ENGLISH SPEAKING AT NUSANTARA MARITIME ACADEMY BANJARMASIN - Muhammad Arinal Rahman; Elisa Rosiana; Moch. Nurdin (Pena Jangkar, 2023)
This study examined the English-speaking barriers faced by marine cadets at Nusantara Maritime Academy in Banjarmasin. This study employed a qualitative, descriptive-analytic approach. In this study, there were 30 participants or cadets; 15 were level 1 cadets in their first semester, and 15 were level 2 cadets in their third semester. Interviews and observation were the tools employed in this study. The statistics showed that the Nusantara Nautical Academy in Banjarmasin's maritime cadets had difficulty speaking English. The issues mentioned were solely the linguistic component of speaking ability, specifically a lack of vocabulary, poor pronunciation, and improper grammar. It was discovered that grammar problems were widespread problem among nautical cadets. Lack of vocabulary was the second challenge maritime cadets encountered. The most recent issue was improper pronunciation.